Pengembangan Model Miniatur Kereta Magnetic Levitation Sebagai Media Pembelajaran Fisika Pada Materi Gaya Magnetik - Andry Fitrian; Iman Noor (UNIVERSITAS INDRAPRASTA PGRI, 2020)
The purpose of this research is to produce a development product in the form of a Magnetic Levitation Train miniature model that can be used by teachers and students in the physics learning process on magnetic force material in class XII. This study uses research and development methods. The research was conducted through several stages, namely the first stage reviewing curriculum standard notes. The second stage is the design of the tool, making a miniature model of the Magnetic Levitation Train and the use of a miniature model of the Magnetic Levitation Train in the learning process. The third stage is the implementation stage, the miniature model of the Magnetic Levitation Train was tested on high school student of class XII to measure students against the miniature model of the Magnetic Levitation Train as a tool to help students understand the concept of magnetic force. The instrument uses a Likert Scale. With three stages, the researcher succeeded in making a miniature model of the Magnetic Levitation Train that was worthy of being one of the learning media on magnetic force material by obtaining information that the validation results by experts, material personnel and students obtained a very good level of measurement which was in the interpretation range of scores 80-100% so it is necessary to develop a miniature model of the Magnetic Levitation Train to be even better in further research.